Congenital nasal pyriform aperture stenosis: Analysis of twenty cases at a single institution. (November 2019) - Shah, Gopi B.; Ordemann, Allison; Daram, Shiva; Roman, Emily; Booth, Tim; Johnson, Romaine; Xi, Yin; Mitchell, Ron
Abstract: Objectives: Congenital nasal pyriform aperture stenosis (CNPAS) is a rare cause of neonatal respiratory distress that is difficult to treat. The primary objective of this study was to identify factors that predict the need for initial and revision surgery for CNAPS. The secondary objective is to identify risk factors in maternal history associated with the development of CNPAS. Methods: Infants with CNPAS between 2010 and 2017 were identified by ICD- 9 and 10 codes. Demographics, maternal history, anatomic features on imaging and medical and/or surgical management were reviewed. Frequencies, means and standard deviations were calculated. A p-value <.05 was considered significant. Results: Twenty infants were included. All underwent flexible nasal endoscopy with inability to pass the scope in either nostril in 65% of infants. Nineteen had a CT scan and 13 had a MRI with midline defects in 76.3% and 53.8%, respectively. Solitary central mega-incisor was present in 65%. Half underwent surgical intervention at a mean age of 74.8 days, with 90% requiring revision surgery. There was no difference in pyriform aperture distance in the surgical and non-surgical patient subgroups (5.4 mm and 5.2 mm, p = .6 respectively). No specific variables were predictive of need for initial or revision surgery. Maternal diabetes mellitus (MDM) was found in 55% of mothers of infants with CNPAS. Conclusion: Pyriform aperture distance was not a predictor of surgical intervention. MRI should be considered in all infants with CNPAS as the rate of intracranial complications is high. MDM may be a risk factor for CNPAS.